Problem-Based Learning (PBL) in Action: Fostering Critical Thinking Among Middle School Students - Sappaile, Baso Intang; Dhaksietsatsura, Virzha Aulianna; Dewi, Eka Olivia; Pinanta, Raden Roro Maya Candra; Yuliyanti, Yuliyanti (PT Inovasi Pratama Internasional, 2025)
This qualitative research study investigates the implementation and effectiveness of Problem-Based Learning (PBL) in fostering critical thinking skills among middle school students. Grounded in constructivist learning theory and Vygotsky's Zone of Proximal Development, this study employed a comprehensive qualitative methodology to examine how PBL influences students' analytical reasoning, problem-solving capabilities, and collaborative learning. Data were collected through semi-structured interviews, classroom observations, focus group discussions, and analysis of student work samples over a 12-week period. Thematic analysis revealed four key themes: enhanced analytical reasoning, collaborative problem-solving, metacognitive awareness, and transfer of learning skills. Findings demonstrate that PBL significantly enhances middle school students' critical thinking abilities through authentic problem-solving experiences that engage them in higher-order thinking processes. The study contributes to the growing body of evidence supporting active learning pedagogies and provides practical insights for educators seeking to implement effective critical thinking instruction in middle school environments.